2021
DOI: 10.1007/s10654-021-00755-3
|View full text |Cite
|
Sign up to set email alerts
|

Season of birth and the risk of dementia in the population‐based Rotterdam Study

Abstract: Early-life environmental factors have been suggested in the pathophysiology of dementia. Season of birth has previously been used as a proxy for these external exposures. We investigated the link between season of birth and the risk of dementia and further explored underlying pathways by studying structural brain changes on MRI. From the Dutch, population-based Rotterdam Study, 12,964 participants born between 1887 and 1960 were followed between 1990 and 2018 for dementia. Cox regression was conducted to asses… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 41 publications
0
2
0
Order By: Relevance
“…In contrast, the cohort study by Mooldijk et al observed a higher dementia risk, especially for AD, for participants born in winter and fall compared to those born in summer. The increased risk was most pronounced in those born in colder winters [79].…”
Section: Season Of Birthmentioning
confidence: 96%
“…In contrast, the cohort study by Mooldijk et al observed a higher dementia risk, especially for AD, for participants born in winter and fall compared to those born in summer. The increased risk was most pronounced in those born in colder winters [79].…”
Section: Season Of Birthmentioning
confidence: 96%
“…The wider effects of season of birth on human brain structure have been investigated using magnetic resonance imaging with winter births associated with increased grey matter volume of the superior temporal gyrus in a study of over 550 individuals [ 23 ]. However, in a larger study of 13,000 Rotterdam Study participants there was no effect of season of birth on any imaging derived measures [ 24 ].…”
Section: Introductionmentioning
confidence: 99%